CRISPR-Cas9 system in autosomal dominant polycystic kidney disease: a comprehensive review - Seungyeon Kang; Se Jin Park; Min Ho Lee; Andreas Kronbichler; Jae Il Shin (Childhood Kidney Diseases)
Genetic kidney diseases are caused by mutations in specific genes that significantly affect kidney development and function. Although the underlying pathogenic genes of many kidney diseases have been identified, an understanding of their mechanisms and effective treatments remains limited. Gene editing, particularly using clustered regularly interspaced short palindromic repeats (CRISPR), has recently become a promising approach for studying genetic diseases and the CRISPR/CRISPR-associated protein 9 (CRISPR-Cas9) method has become a prominent research method. It has been shown that CRISPR-Cas9 can be targeted to knock out specific genomic sites, which enables researchers to correct gene mutations, prevent inheritance, and better understand the function of genes and the effectiveness of drugs. However, the application of CRISPR-Cas9 technology in the development of therapeutic agents against genetic kidney disease has been overlooked compared with other genetic diseases. In this paper, we provide an overview of the current research advancements in genetic kidney diseases using CRISPR technology, as well as the diverse preclinical research methods implemented, with particular emphasis on autosomal dominant polycystic kidney disease.